IL-17 Expression in Dermatitis Herpetiformis and Bullous Pemphigoid - Agnieszka Zebrowska; Malgorzata Wagrowska-Danilewicz; Marian Danilewicz; Olga Stasikowska-Kanicka; Anna Cynkier; Anna Sysa-Jedrzejowska; Elzbieta Waszczykowska (Mediators of Inflammation)
Dermatitis herpetiformis (DH) and bullous pemphigoid (BP) are skin diseases associated with eosinophilic and neutrophilic infiltrations. Although cytokines are critical for the inflammatory process, there are single findings concerning concentration of IL-17 in bullous diseases. The goal of this study was to assess IL-17 expression in DH and BP patients. Skin biopsies were taken from 10 DH, 14 BP patients and from 10 healthy subjects. The localization and expression of IL-17 was studied by immunohistochemistry and the serum concentration was measured by immunoassays. Expression of IL-17 in the epidermis and in influxed cells in dermis was detected in skin biopsies. Expression of IL-17 was statistically higher in epidermis and infiltration cells in specimens from BP than from DH patients. Examined interleukin expression was detected in perilesional skin of all patients but it was much lower than in lesional skin. The expression of IL-17 was not observed in biopsies from healthy people. Serum level of IL-17 was statistically higher in BP and DH groups as compared to control group. Our results provide the evidence that IL-17 may play an essential role in activating and recruiting eosinophils and neutrophils, which ultimately contribute to the tissue damage in DH and BP.